The Nigeria Independent Accountability Mechanism for maternal, newborn, and child health. Issue 1 (17th July 2014) - Garba, Aminu Magashi; Bandali, Sarah
Abstract: Since the 2010 launch of the UN Secretary‐General's Global Strategy for Women's and Children's Health, worldwide political energy coalesced around improving the health of women and children. Nigeria acted on a key recommendation emerging from the Global Strategy and became one of the first countries to establish an independent group known as the Nigeria Independent Accountability Mechanism (NIAM). NIAM aims to track efforts on progress related to Nigeria's roadmap for the health of women and children. It includes eminent people from outside government to ensure independence, and is recognized within government to analyze and report on progress. The concept of NIAM received approval at various national and international forums, as well as from the Nigeria Federal Ministry of Health. This experience provides an example of connecting expertise and groups with the government to influence and accelerate progress in maternal, newborn, and child health. Engagement between government and civil society should become the norm rather than the exception to achieve national goals.